Serviço social e educação popular : caminhos que se cruzam na direção de processos emancipatórios - Vargas, Tatiane Moreira de (2014)
This study discusses the relationship between Social Work and Popular Education, considering the socio-educational dimension of professional work of the social worker. The purpose of it was to analyze how the production of knowledge in the field of social work expresses the similarities between Social Work and Popular Education in order to identify and strengthen emancipatory processes. Considering, among other factors, the incidence of meetings between Social Work and Popular Education, produced in the context of Health Policy, the study also presents an analysis of Ordinance No. 2761 of 11/19/2013 establishing the National Education Popular in Health Policy as current rules providing for Popular Education as normative, under the Unified Health System. The research was the qualitative type, bibliographic and documentary, with epistemological orientation of dialectical-critical method. Were defined as study universe theses and dissertations in the area of Social Work, the productions published on events and periodic greater national impact area of Social Services, the period of 2006 - 2014. Whereas professional actions must meet the commitment ethical-political assumed as Social Worker in everyday coping with expressions of Social Issues, Popular Education may provide important information for formation and professional performance, with assumptions to support the pedagogical relationship that sets the social and educational dimension of Social Work, direction of emancipatory processes, in that both have as towards human emancipation. In this sense, the social and educational dimension of social work should be a "Socio-Educational Popular Dimension", indicating the education approach that meets the intent of their actions. There is the expectation that the actual outcomes may instigate new critical reflections in a constant movement of thinking about practice ethically and politically committed and and dare to do and redo the practice, realizing "viable-unpublished”.